Transforming Indonesian Primary Education Through Creativity Development in the 21st Century - Sari, Kartika; Siswadi, Siswadi (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This research aims to analyze the urgency and strategies for developing creativity in basic education in Indonesia, especially in elementary schools, as the foundation for the formation of human resources that are adaptive, innovative, and ready to face the challenges of 21st century education. Methodology: This study used a standard printed questionnaire without a brand, manual observation sheets, and photo documentation using an Android phone camera (Samsung Galaxy A series). The methods applied include descriptive qualitative approaches, thematic analysis, literature studies, student surveys, and teacher reflection. The software used is Microsoft Word 2019 and Mendeley Desktop. Main Findings: The development of creativity in elementary schools has been shown to increase students' learning motivation by 41% and ecological awareness by 24%. Project-Based Learning and the Learning Cycle approach are effective in encouraging creative thinking across subjects. The role of teachers as creative role models is a key factor in creating a safe, participatory, and classroom climate oriented towards the originality of ideas and contextual problem solving. Novelty/Originality of this study: The novelty of this research lies in the integration of the 4P framework of creativity with empirical data on student voices and teacher reflections in rural elementary schools. This study shows that environment-based contextual creativity and PjBL not only increase learning motivation, but also ecological awareness. These findings broaden the understanding of creativity development as an adaptive strategy for primary education in the VUCA era.